STUDI TENTANG KUALITAS HASIL REPAIR WELDING PADA CAST WHEELS ALUMINIUM DENGAN METODE PENGELASAN OKSI ASETILIN, TIG DAN MIG TERHADAP SIFAT FISIS DAN MEKANIS - Kusmanto, Kusmanto (Jurnal Nosel, 2013)
The purposes of this research are: (1) To determine the effectchemical composition and microstructure of arearepairweldingresultswithoxyacetylene, TIGandMIG weld methodon aluminium castwheels. (2) To determine thehardnessand impact toughnessathigh of arearepairweldingresultswithoxyacetylene, TIGandMIG weld methodon aluminium castwheels. The research has donein the laboratory ofINLASTEKSurakarta. Type of this research is descriptive qualitative uses experimental methods.The Object  in this research used arealuminium castwheels. Techniques of data analysis in this research using descriptive data analysis that is directly observed experimental results are then analyzed and summing up the results of the research. As an input parameter in analyzing the data include:the testing of chemical composition, microstructure, hardnessandimpact. From  the research, we can conclude that the chemical compositionon aluminium castwheelsincludingalloyAluminum Silicon, because the element Si alloyisthe largest, ie7.38%Si. The highesthardness number ofoxyacetyleneweldingresultsby54.80BHNinthe weld areaand38.69BHNinthe HAZ. The lowesthardness number ofMIGweldingresultsby44.18BHNinthe weld areaand TIG welding results by 38.69BHNinthe HAZ. The highestimpact number ofresults TIG welding with impact number average0.114joules /mm². The lowestimpact number ofresultsoxy-acetylene welding with impact number average0.085joules/mm².